Aerobic, resistance and combined exercise training for patients with amyotrophic lateral sclerosis: a systematic review and meta-analysis. (December 2021) - Rahmati, Masoud; Malakoutinia, Fatemeh
Abstract: Objective: The aim of this systematic review and meta-analysis was to assess the effect of aerobic, resistance and combined exercise training in patients with ALS. Data source: A comprehensive systematic search of CENTRAL, CINAHL, SPORTDiscuss, Embase, Scopus, ProQuest was performed from inception to February 2021. Eligibility criteria: The systematic review included all studies that examined the effect of exercise training in ALS patients. Meta-analysis was also carried out on randomized controlled trials (RCTs). Data extraction and data synthesis: Data related to primary outcomes (functional ability, respiratory function, fatigue, pain, quality of life, upper-body strength, lower-body strength and Vo2 peak) and secondary outcomes (adverse events and feasibility of exercises) was extracted from all studies and systematically reviewed. Results: 16 trials including 532 patients met the inclusion criteria; of these, eight studies were included in this meta-analysis. The meta-analysis found a statistically significant difference in favor of exercise in functional ability ( P = 0.001), overall quality of life ( P = 0.03) and Vo2 peak ( P = 0.01). The included trials were generally of poor quality and had a risk of bias. However, the results of sensitivity analysis, after omitting studies with high risk of bias, showed no statistically significant difference in functional ability ( P = 0.05), overall quality of life ( P = 0.12) and Vo2peak ( P = 0.13). Finally, no significant difference was found in respiratory function, fatigue, pain, and upper-body and lower-body strength. Conclusions: The safety and effectiveness of exercise therapy in ALS patients remains unclear and further high quality RCTs with larger sample size are needed. Systematic Review Registration Number PROSPERO CRD42019140011